Avaliação das características físico-químicas e microbiológicas de carne mecanicamente separada de frango de diferentes marcas comerciais. - Felipe Coser Chow (2011)
Since the latest 50s, mechanically deboned chicken meat (MDCM) has been used by industry as a raw matter for meat products. Such practice has become quite usual nowadays and because of productive and behavior reasons and even due to his high offer in market, it presents a continuous growing outlook. It is known also that such a meat has very particular characteristics due to its processing and because of the raw matter used in its production. The Ministry of Agriculture, Livestock and Food Supply (MAPA) sets the quality characteristics of MDCM concerning both microbiological and physic chemical profile, which have to be followed by the producers. In this way, five different MDCM brands, numerically identified (1 to 5) and formed by six samples from different batches each were evaluated for some parameters defined by MAPA. The microbiological analyses performed in meat matrix were Salmonella spp., Staphylococcus aureus and Clostridium perfringens, based on the acceptance criteria established by MAPA. It was also evaluated the following proximate analysis moisture, protein, fat, ash, peroxide index (PI). Judging the microbiological results, no brands were disapproved for C. perfringens, but two were disapproved in Salmonella spp. analysis once they exceeded the limit of acceptance for the test (c>2). The mean counting for S. aureus was 2,55 log UFC/g; 3,04 log UFC/g; 2,74 log UFC/g; 2,05 log UFC/g; and 3,05 log UFC/g for brands 1 to 5, respectively, which meant a 80% brands disapproval. The moisture mean values were in accordance with literature, showing variations of 61,0% to 68,8%. Based on MAPA physic chemical characteristics of quality, the mean protein values varied between 9,9% and 15,4% and two brands (2 and 5) were disapproved since they presented mean values under 12% ( 9,9% e 11,7%, respectively). The brands fat mean values varied from 14,5% to 28,7%, following the limits established by MAPA (max. 30%), although two batches of one brand were disapproved as they exceeded the limit of 30% established. The ash mean values varied from 0,7% to 1,1%. The peroxide index (IP) mean, established by MAPA in 1 mEq per kg of fat maximum, varied between 1,7 and 15,9 mEq/kg, causing a 100% brands disapproval. The disaccord of microbiological and proximate analysis results with Brazil standart regulations are indications that private and fiscal quality and self control programs should be improved. New studies should be performed to comprehend better and to get to know more about MDCM frozen stored oxidative behavior in relation to its raw matter quality and post production time.